2015
DOI: 10.1016/j.jinteco.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal consolidation with tax evasion and corruption

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 25 publications
3
56
0
Order By: Relevance
“…The conclusions in Alesina et al (2015b) support previous studies, emphasizing that tax-based consolidations produce deeper and longer recessions than spending based ones. Pappa et al (2015) study the impact of fiscal consolidation episodes in an environment with corruption and tax evasion, and find evidence that fiscal consolidation causes large output and welfare losses. They find that much of the welfare loss is due to increases in taxes, which creates the incentives to produce in the less productive shadow sector.…”
Section: Related Literaturementioning
confidence: 99%
“…The conclusions in Alesina et al (2015b) support previous studies, emphasizing that tax-based consolidations produce deeper and longer recessions than spending based ones. Pappa et al (2015) study the impact of fiscal consolidation episodes in an environment with corruption and tax evasion, and find evidence that fiscal consolidation causes large output and welfare losses. They find that much of the welfare loss is due to increases in taxes, which creates the incentives to produce in the less productive shadow sector.…”
Section: Related Literaturementioning
confidence: 99%
“…Pappa, Sajedi and Vella concluded that output drops in Portugal were presumably caused by the tax-based consolidation package (Pappa et al 2015). Erceg and Linde presented supporting conclusions for expenditure cuts, but pointed out that this may not be true for the economy, which is constrained by the currency union membership (Erceg and Linde 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These methods include the structural equation model (SEM) and the dynamic stochastic general equilibrium (DSGE) model. The former examines statistical links between observed and unobserved variables (see, for example, Frey and Weck-Hanneman (1984), Buehn (2011), Wiseman (2013), whereas the latter is based on the rational behavior of agents (see, for example, Orsi et al (2014), Argentiero and Bollino (2015), Pappa et al (2015), or Annicchiarico and Cesaroni (2016)). …”
Section: Measurement Of the Shadow Economymentioning
confidence: 99%